Plasma trace mineral profilingviz-a-viz estrus induction using mineral supplementation in post-partum anestrous crossbred cow of the Kashmir valley - GhRasool Bhat; Sabia Akhter; Mohd Iqbal Yatoo; FaroozAhmad Lone; Jalal U Din Parrah (The Indian Veterinary Journal, 2024)
The study was conducted on crossbred dairy cows (n=30) with the history of anestrum for more than 90 days postpartum. Animals in the present study two groups viz; Group I- (n=20) which were treated with mineral mixture (@50gm/day) and Group II (n=10 control) -anestrous cows advised to wait for more than 42 days without any treatment. The animals were subjected to two ultrasonographic examinations of reproductive tract and ovaries at 10 days interval, to confirm anestrum by presence of smooth ovaries (small follicles 4-5mm in diameter and absence of CL). Blood samples werecollected on day 0 (start of treatment or second ultrasonographic examination), day 21 (one cycle length) and day 60 of oral mineral supplementation. Plasma was separated and stored at -20o, until analysis. Using flame absorption spectrophotometry, copper (Cu), zinc (Zn), iron (Fe), manganese (Mn) and cobalt (Co) levels in plasma were estimated in both the Group I and II. Animals which exhibited the signs of estrus had a clear cervicovaginal mucous discharge and a dominant follicle at one ovary. It was concluded that 1) mineral supplementation induced cyclicity in anestrous cows with acceptable conception rate and 2) Plasma Zn and Fe levels significantly increased on day 60 while Cu, Mn and Co levels didn’t improve by 60 days supplementation period. It can be concluded from this study that mineral deficiencies or alteration in mineral dynamics might serve as important cause of postpartum anestrum in dairy crossbred cows and oral supplementation of chelated minerals @50g/animal/day for at least 60 days is beneficial in induction of fertile estrus in postpartum anestruscows.